NITROGEN AND PHOSPHORUS AS KEY ELEMENTS OF MODERN AGRICULTURE - Botirova Sabogul Rahmatullayevna; Pirnazarova Sevinch O‘ktam qizi (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Nitrogen and phosphorus are essential macronutrients that play a fundamental role in modern agricultural systems. This article examines the significance of these nutrients in plant growth, development, and yield formation. Particular attention is given to the physiological functions of nitrogen and phosphorus, their role in photosynthesis, energy transfer, root development, and crop productivity. The interaction between nitrogen and phosphorus and the importance of their balanced application for efficient nutrient uptake are also discussed. Furthermore, the paper addresses environmental considerations associated with the excessive use of mineral fertilizers and emphasizes the necessity of scientifically based and sustainable nutrient management practices. The findings highlight that the rational use of nitrogen and phosphorus fertilizers is crucial for maintaining soil fertility, improving crop yields, and ensuring environmental sustainability in modern agriculture.